Joint "Social Marketing" Promotion of a Weaning Food and a Contraceptive in Sri Lanka - FARLEY, John U. (Institutional Knowledge at Singapore Management University, 1980)
Experimental combinations of promotions and offers of free samples of a weaning food and a contraceptive were sent by mail to a sample of Sri Lankan households with recently born children. Based on responses to an initial mailing and a follow-up, promotions and offers significantly affected behavior, with impact greater for the weaning food than for the contraceptive. No significant gain in response resulted from joint promotions, but cost savings made joint promotion of both products to the same target group cost effective.